Green Lantern. Vol. 3, Power of will - Adams, Jeremy (Screenwriter); Tomasi, Peter; Guggenheim, Marc; Johnson, Phillip Kennedy, 1970-; Jurgens, Dan; Marz, Ron (DC Comics, 2025)
The seeds of war have been sown across the galaxy and now it's up to Green Lanterns Hal Jordon, John Stewart, and Guy Gardner to stop it! But how far will they have to go, and what, exactly, is the secret of the Dark Star resurrection? The Green Lanterns must deal with the fallout of Absolute Power and Green Lantern: War Journal in ways that will change the DC Universe's cosmos forever! The Dark Star ring represents a dangerous and mysterious threat that only Hal, John, and Guy can get to the bottom of! But how far will they go, and where will this path take them? A brand new era of Green Lantern stories start here!--